A wireless MAN in Bragança - digital city - Rufino, José (2016)
Following the portuguese Digital Cities Program, twelve Information Society related projects where initiated in the city of Bragança, under a common goal: “to reduce interiority costs”. A wireless network with metropolitan coverage was then built to fulfill the communication requirements, both between institutions and to the Internet. We present here several important design decisions and implementation issues that took place, ranging from wireless protocol choosing, to topology, addressing, routing, scalability considerations, as well as a preliminary performance evaluation. In the end, our wireless MAN proved to solve the connectivity problems, both by providing a performant and economical solution, suited to the application scenario.